(untitled) (Medico Legal Update, 2020)
The origin of renal arteries, vessel diameter, and point of entry to the kidney has all been analyzed as potential parameters which are a clinically relevant issue. This anatomical feature may be essential for fully understanding the process of renal perfusion, as it is not only the number of renal arteries that influences the extent of renal blood supply, also their diameter. The aberrant renal arteries that supply the inferior pole are more important because it provides arterial supply to the proximal part of the ureter. The objective of this study is to identify influences and prevalence of aberrant renal arteries of the kidney donors’ cases to perform role of the aberrant renal artery. Prevalence of aberrant renal artery was identified in 26.3% of the cases, incidence was more frequent in left than right side; about 78.7 % of cases presented unilaterally. The remaining cases 21.2 % were RAs presented bilaterally. Diameter of main RA in kidney presenting the RA was 5.73 mm and that of kidney with only single renal artery was 6.19 mm.